Transitional dynamics and the evolution of information transparency: A global analysis; Dinámica transicional y evolución de la transparencia en la información: un análisis global - Andrew Williams; Tsun Se Cheong; Michal Wojewodzki (Estudios de Economía, 2022)
The last quarter of the 20th century was a period of sustained economic growth across many countries. Countries' institutional arrangements have been commonly employed as factors in the convergence studies of economic growth and income levels. However, the issue of whether institutions themselves converge has been under-researched. Using the nonparametric distribution dynamics approach and a sample of 194 countries during the 1980-2010 period, we examine a tendency for countries' informational transparency (IT) to converge over time. We find that whilst there is some evidence of unconditional convergence across countries, there is stronger evidence for convergence clubs to emerge, at both regional and income levels. Notably, the level of IT of the low- and lower-middle-income countries and those situated in Africa, and Middle East regions tend to converge towards a level significantly below the global average. We also find a strong relationship between income and IT.
Keywords: C4; E02; F55; P48; 330; Institutional convergence; Information transparency; Convergence clubs; Distribution dynamics; Mobility probability plot